Peruvian President’s Approval Rating Based on Sentiment Analysis on Tweet Data - Solis Navarro, Luis Fernando (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The popular acceptance rate is a concept used to explain the increase in popular support for a political figure in a country over a given period. This figure is extracted through requested surveys that reach a certain limited sample of willing citizens and are expensive to conduct. In this research we have implemented an automatic system for estimating the popular approval of the president of Peru using Twitter data. The method is simple, fast and highly sensitive, and can be quickly extended to other cases of opinion analysis.